FE-NI ALLOY COLD-ROLLED SHEET AND ITS PRODUCTION - SAKURATANI TOSHIKAZU; NOZAKI TSUTOMU; KITAOKA HIDENARI; ARIMA YOSHIHIRO; SUZUKI TSUKASA (1987)
PURPOSE:To improve surface characteristics, electric conductivity, and heat resistance by controlling the composition of nonmetallic impurities formed out of a deoxidizer as an additive to Al2O3-MnO-SiO2 composition having superior hot drawability in refining an Fe-(30-45%)Ni alloy. CONSTITUTION:In refining the Fe-(30-45%)Ni alloy, the amounts of Si, Mn, and Alsol, added as deoxidizer, contained in the alloy are regulated to 0.1-0.3%, 0.3-1%, and 0.0004-0.002%, respectively, and the composition of nonmetal existing in the above alloy is also regulated to Al2O3-MnO-SiO2. Then this casting is soaked to 1,100-1,300 deg.C and hot-rolled. The composition of the nonmetals severally existing in the above alloy is regulated so that it is within the area enclosed with a line connecting the points from 1-5 in the ternary diagram shown in the figure.